Pengaruh Bauran Pemasaran terhadap Kepuasan dan Loyalitas Pelanggan Mesari Luxury Villas Bali - Rachmi Anugerah Mahmud; Jusni Jusni; Andi Nur Baumassepe (Hasanuddin Journal of Business Strategy, 2019)
Marketing, which has a lot of roles in lodging services, among others, provides services to consumers with friendly satisfaction, provides adequate facilities and operates to benefit.This study aims to determine the effect of Marketing Mix on Customer Satisfaction and Loyalty of Bali's Mesari Luxury Villas. This study uses a descriptive approach and verification research. Descriptive research is research that aims to obtain a description of the characteristics of variables (marketing mix strategy, loyalty and satisfaction). Verification research is a type of research that aims to determine the relationship between variables through a hypothesis testing using path analysis methods with the help of Smart PLS 3.2.8 application. The results showed that partially the marketing mix had a positive and significant effect on customer satisfaction, the marketing mix had a positive and significant effect on customer loyalty, and satisfaction had a positive and significant effect on customer loyalty. The influence indirectly shows that customer satisfaction can mediate the influence of the marketing mix on customer loyalty positively and significantly